PENERAPAN MINDFULNESS ISLAMI DALAM MENINGKATKAN PENGENDALIAN DIRI SISWA SMK (Studi Kasus di SMK Al-Ikhlas Batujaya Karawang) - Hilaliah, Dila; Oyoh Bariah; Afiyatun Kholifah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of Islamic mindfulness in improving self-control among vocational high school students at SMK Al-Ikhlas Batujaya Karawang. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation involving Islamic Education teachers, student affairs teachers, and students as key informants. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was strengthened through source and technique triangulation. The findings show that Islamic mindfulness was implemented through religious habituation activities, including Qur’an recitation, congregational prayer, dhikr, prayer, muraqabah, muhasabah, patience, sincerity, and tawakal. These activities helped students develop spiritual, emotional, cognitive, and behavioral awareness. Improved self-awareness encouraged students to manage anger, delay impulsive reactions, consider the consequences of actions, and direct their behavior toward more positive and disciplined conduct. Supporting factors included a religious school culture, teacher guidance, routine religious activities, and student participation. Inhibiting factors included peer influence, excessive social media use, and unstable internal motivation. The study concludes that Islamic mindfulness can serve as a relevant character education strategy for strengthening students’ self-control in Islamic-based vocational education.